Background Paper on Government Tools for Sector Sustainability - Eftimie, Adriana (World Bank, Washington, DC, 2014)
This chapter examines overarching mineral policies and mining laws to identify current trends in mineral development that contribute towards sustainable development. From those trends key components are defined that, if embedded in overarching policy and legal instruments, becomes tools of sustainability.